MODEL PEMBELAJARAN INKUIRI TERBIMBING DENGAN APLIKASI ZOOM UNTUK MENINGKATKAN PROSES DAN HASIL BELAJAR FISIKA MATERI LISTRIK DINAMIS - Yissia Efli Risli Buka; Tineke Makahinda; Alfrits Komansilan (Charm Sains: Jurnal Pendidikan Fisika, 2021)
The guided investigation is a varied process and includes observing activities, formulating relevant questions, performing experiments, or experiments on students. Research on guided exploratory learning models with zoo applications to improve the process and learning outcomes of physical dynamic electrical material. This study aims to determine the Inkuri guided learning model with the Zoom application to improve the process and learning outcomes of dynamic electrical materials physics. This research was carried out on SMA N 1 Remboken in Class XII IPA 1 and XII IPA 2. This research method is experimental research. Research data based on post-test results. The average learning outcomes of students treated with the guided query learning model using the Zoom application was 64.966667 with a maximum score of 87 and a minimum score of 46. While the average learning outcomes of students who were treated with the Zoom application Application guided learning without guided inquiry were 58.48387097 with a maximum score of 78 and a minimum score of 44. From the data, the data normality test was performed, which showed Lcount <Ltable, which means that the experimental and control class data were normally distributed, then a hypothesis test was carried out. Data on student learning outcomes from the post-test. The results of the research by calculating the one-way T-test formula show that in the learning model for guided queries with the zoom application, the value of tcount = 2.9920534101 > ttable = 2.00099538 and then H0 is rejected. It can therefore be concluded that the average learning outcomes of the students using the guided inquiry learning model with the Zoom application are higher than the average learning outcomes of the students using the guided inquiry learning.